السياسة التشريعية في الجزائر وتأثيرها على الحريات العامة - نور الهدى بعرور; مريم بوحصان (My University, 2018)
Summary: Public freedoms occupy an important place in various political systems, contrary to their place and time. They are evidence of man's humanity, which distinguishes him from all other creatures and a source of various fundamental rights. Because of this importance, the various Algerian constitutions, starting with the Constitution of 1963 and the last amendment of 2016, have protected them, guaranteed their exercise and referred their organization to law. s rights ", which inevitably affects these freedoms by expanding their protection for the realization of the rule of law or by narrowing their scope whenever necessary to protect public order in its broad sense, which reflects the time-consuming conflict between power and freedom, Within this framework, this study dealt with two chapters, the first chapter including The legal framework of Algeria's legislation and public freedoms, and a second chapter incorporating manifestations of the impact of legislative policy on public freedoms. .......................... الملخص: إن الحريات العامة تحتل مكانة هامة في مختلف الأنظمة السياسية بإخلاف مكانها وزمانها ذلك انها دليل إنسانية الانسان التي تميزه عن سائر المخلوقات ومصدر لمختلف حقوقه الاساسية ونظرا لهذه الأهمية التي تكتسيها فقد تناولتها مختلف الدساتير الجزائرية بدء من دستور 1963 وصولا إلى آخر تعديل سنة 2016 فكفلت حمايتها وضمان ممارستها وأحالت تنظيمها للقانون متبعة، في ذلك سياسة تشريعية معينة و التي تأثير لا محالة على هذه الحريات إما بتوسيع مجال حمايتها تحقيقا لدولة القانون وأما بتضييق مجالها متى ما دعت الضرورة إلى ذلك حماية للنظام العام بمفهومه الواسع وهو ما يجسد الصراع الأزلي بين السلطة والحرية، وفي إطار ذلك فقد تناولت هذه الدراسة فصلين , فصل أول يتضمن الإطار القانوني التشريع والحريات العامة في الجزائر ، وفصل ثاني يتضمن مظاهر تأثير السياسة التشريعية على الحريات العامة. ................... Résume : La liberté générale est Primordiale dons tous les systèmes politique et dons toutes temps. Elle est défini par l’humorisme de l’être humain qui se diffère de tout autre être vivant, c’est une source de ses droit es esenciel, et donc toutes les constitutions Algérienne l’a appris en considération depuis 1963 jusqu’au dernier réforme de la constitution de 2016. Ils ont pris en charge leurs application par des lois organisées et une politique précise qui s’influés sur ces libertés les de fendre et l’élargir dans un état de droit ou la réduire si cela est nécessaire pour le bien de l’ordre publique, et ce qui pose des problèmes tout le temps entre les autorités et la liberté ; En déduit cette étude de deux chapitre Chapitre I :Il comprend la cote de compréhension et des lois dans le travail législative en Algérie Chapitre II : Il comprend des signes d’en fluence sur la liberté générale.